Establishment of mathematical model for minimization of human energy in a plastic moulding operation. (2021) - Dhutekar, Prashant; Mehta, Girish; Modak, Jayant; Shelare, Sagar; Belkhode, Pramod
Abstract: This article deals with the field data study and analysis to estimate and optimize human energy expenditure for the plastic injection moulding process. The article explains the formulation of a field data-based mathematical model for human energy expenditure. The data-based field model is proposed with optimized variables for reducing human energy consumption in various operations involved in the plastic injection moulding process, thereby increasing productivity. The independent variables influencing the phenomenon (Human Energy Consumption in Plastic Moulding Operation), such as anthropometric variables of workers, environmental variables, and workstation variables, are the part of this study. For this, research has been undertaken to formulate the model through dimensional analysis techniques, which is then accompanied by the analyses, including optimization and sensitivity. Buckingham's pi theorem (BPIT) is used to group the variables into pie terns in order to establish the mathematical model. Linear programming with Ms-solver is used to optimize and determine the optimized value of pie terms to minimize human energy.